IMPLEMENTASI KERJASAMA INDONESIA DAN AMERIKA SERIKAT PADA BIDANG PENGUATAN KAPASITAS DAN KEMAMPUAN DALAM PENANGGULANGAN KASUS TERORISME PERIODE 2018-2021 - Farhan Fatah Dasopang (2023)
Terrorism is an act that is threatening and can disturb the peace of human life. Today, acts of terrorism are happening all over the world and affecting innocent people. In recent years, there have been several cases of terrorism that have occurred in Indonesia and the United States. The situation of the two countries like this is very concerning for the security of the country. The government should have noticed and prioritized something like this. To improve state security capabilities, Indonesia needs to carry out cooperation between countries (internationally). In this study, the author will discuss cooperation between Indonesia and the United States in the field of strengthening capacity and capability in countering terrorism cases. This can be achieved by the existence of programs that are carried out such as information exchange, training and education, as well as weapons assistance. This research uses descriptive qualitative research methods. The author also uses several journal articles and conducts interviews with relevant agencies to complete the necessary data. In this research, the author also uses several theories, including National Security, Terrorism, Security Diplomacy, and the Capicity Building. The results of the study show that the implementation of cooperation between Indonesia and the United States is going well. This can be proven by the decrease in acts of terrorism throughout 2021, which was 53.8% compared to 2020.